Semilinear elliptic equations involving mixed local and nonlocal operators - Biagi, Stefano; Vecchi, Eugenio; Dipierro, Serena; Valdinoci, Enrico (Proceedings of the Royal Society of Edinburgh. Section A. Mathematics, 2021)
In this paper, we consider an elliptic operator obtained as the superposition of a classical second-order differential operator and a nonlocal operator of fractional type. Though the methods that we develop are quite general, for concreteness we focus on the case in which the operator takes the form − Δ + ( − Δ)s, with s ∈ (0, 1). We focus here on symmetry properties of the solutions and we prove a radial symmetry result, based on the moving plane method, and a one-dimensional symmetry result, related to a classical conjecture by G.W. Gibbons.